PENERAPAN SILENT READING TECHNIQUE DALAM MENINGKATKAN PEMAHAMAN TEKS BAHASA ARAB MAHASISWA (Studi Kasus Pada Mata Kuliah Bahasa Arab I di Prodi Pendidikan Agama Islam Kelas B) - Junanah Junanah; Nursalim Nursalim (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2016)
This study is based on the finding that the Students of Islamic Education Department, Faculty of Islamic Studies, Indonesian Islamic University (UII), Academic Year 2015/2016 has a low ability to understand the Arabic text. It is felt necessary improve the ability to understand the Arabic text. As a real step been the application of silent reading technique. The results showed an increase in Arabic text comprehension abilities of students. As evidence is the increase in the their average result in the first cycle and the second cycle. This increase is accompanied by an increase in the quality and innovation of learning Arabic.